2010
DOI: 10.1186/1471-2407-10-343
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic transformation of breast epithelial cells by genotoxic stress

Abstract: BackgroundExposure to genotoxic stresses such as radiation and tobacco smoke can cause increased cancer incidence rate as reflected in an in depth meta-analysis of data for women and breast cancer incidence. Published reports have indicated that exposures to low dose radiation and tobacco smoke are factors that contribute to the development of breast cancer. However, there is a scarcity of information on the combinatorial effects of low dose radiation and tobacco smoke on formation and progression of breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Cells also appeared more rounded with increasing radiation dose. These observations were similar to what had been previously reported on irradiated MCF-7 and normal breast epithelial cells [9,10]. Alteration in plasma membrane morphology and reorganization of actin filament close to the plasma membrane had also been reported.…”
Section: Effects Of Gamma Radiationsupporting
confidence: 81%
“…Cells also appeared more rounded with increasing radiation dose. These observations were similar to what had been previously reported on irradiated MCF-7 and normal breast epithelial cells [9,10]. Alteration in plasma membrane morphology and reorganization of actin filament close to the plasma membrane had also been reported.…”
Section: Effects Of Gamma Radiationsupporting
confidence: 81%
“…The response of breast epithelial cells and breast cancer cell to cigarette smoke has been previously examined [15,16,30,31], but these studies focused on short-term treatment (up to one week) while we have analyzed the effect of continuous long-term exposure. We demonstrated that chronic exposure to tobacco smoke in the form of CSE or CSC can alter the phenotype of mammary epithelial cells, promoting the acquisition of mesenchymal traits such as increased anchorage-independent growth, motility, invasion, and the expression of markers associated with self-renewal and tumor initiation.…”
Section: Discussionmentioning
confidence: 99%
“…One such agent is the environmental pollutant, benzo[a]pyrene diol epoxide (BPDE), which can form stable DNA adducts [ 5 – 7 ]. Previously, our laboratory reported the oncogenic role of BPDE in human breast epithelial cells [ 8 ] and identified an RNA helicase, DDX3X (DDX3), as a contributing factor [ 9 ]. We demonstrated that DDX3 was upregulated after exposing immortalized non-tumorigenic breast epithelial cells, MCF 10A, to BPDE.…”
Section: Introductionmentioning
confidence: 99%